2015
DOI: 10.1002/chin.201541002
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Infinitely Adaptive Transition‐Metal Ordering in Ln2O2MSe2‐Type Oxychalcogenides.

Abstract: Infinitely Adaptive Transition-Metal Ordering in Ln 2O2MSe2-Type Oxychalcogenides. -A range of Ln 2O2 Se2 and La2-yCeyO2M 1 Se2 (Ln: La, Ce, M 1 /M 2 : Fe, Zn, Mn, Cd) solid solutions are prepared (60 new compositions) to investigate the effects of systematically changing the relative sizes of [Ln 2O2] 2+ and [MSe2] 2layers on transition metal ordering by powder X-ray and neutron diffraction. Transition metal ordering is determined by the relative sizes of the [Ln 2O2] 2+ and [MSe2] 2layers and can be exquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The Cr1 (Cr 2+ ) moment is similar in direction and magnitude to the Cr 2+ moment in the analogous layers in both Ba 2 CrO 2 Cr 2 As 2 and Sr 2 CrO 2 Cr 2 As 2 , 14,15 where the CrO 2 layers are also antiferromagnetic, therefore also supporting the assignment of the Cr1 oxidation state as Cr 2+ . Furthermore, bond valence sums (calculated using bond length data provided by Brese and O'Keefe 39 and where the literature Cr−As bond length used was that for Cr II −As in both cases as a known Cr III −As bond length was not found) corroborate with this assignment as these give Cr1 an oxidation state of +2.090(2) and Cr2 an oxidation state of +2.980 (8). The observed antiferromagnetism, the bond valence sums, and the sizes of the ordered moments are consistent with a lack of mixed valency on the Cr1 and Cr2 sites.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
“…The Cr1 (Cr 2+ ) moment is similar in direction and magnitude to the Cr 2+ moment in the analogous layers in both Ba 2 CrO 2 Cr 2 As 2 and Sr 2 CrO 2 Cr 2 As 2 , 14,15 where the CrO 2 layers are also antiferromagnetic, therefore also supporting the assignment of the Cr1 oxidation state as Cr 2+ . Furthermore, bond valence sums (calculated using bond length data provided by Brese and O'Keefe 39 and where the literature Cr−As bond length used was that for Cr II −As in both cases as a known Cr III −As bond length was not found) corroborate with this assignment as these give Cr1 an oxidation state of +2.090(2) and Cr2 an oxidation state of +2.980 (8). The observed antiferromagnetism, the bond valence sums, and the sizes of the ordered moments are consistent with a lack of mixed valency on the Cr1 and Cr2 sites.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
“…Our previous work on single-metal layered oxychalcogenides has shown that the combination of a rigid oxide layer and a more flexible chalcogenide layer can lead to structures with remarkable complexity and large superstructures in the ab plane. 14,15 In this work, we have shown that a similar level of complexity can be built into these materials along the stacking direction by using two metals, giving rise to the range of materials from 4Cd/1Cu to 1Cd/4Cu shown schematically in Figure 2. Although we use a conventional description in this − ordering mode which leads to a checkerboard ordering within layers and adjacent layers with Cd positions offset by (1/2, 1/2) in the ab plane such that layers repeat in an ABAB sequence along c. This arrangement would be expected purely on electrostatic grounds and is retained within the Cd blocks of all our materials.…”
Section: ■ Discussionmentioning
confidence: 92%
“…We have previously described how combining rigid-geometry oxide building blocks with more flexible or adaptive chalcogenide layers can lead to infinitely adaptive structures with remarkable structural complexity (though governed by simple rules) in two dimensions. 14,15 Here we show that this complexity can be extended to three dimensions in a new family of mixed-metal oxychalcogenides. We unravel their crystal chemistry from powder diffraction studies, despite stacking faults leading to nonroutine peak shapes.…”
Section: ■ Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…These compounds adopt a layered, ZrCuSiAs-related structure with modulated transition-metal selenide layers with a (3 + 1)dimensional structure in the superspace group Cmme(α01/ 2)0s0. 9 Further polymorphs exist with T = Mn and Fe, respectively. To distinguish the polymorphs, we extended the formulas by the Pearson letters.…”
Section: ■ Introductionmentioning
confidence: 99%